PKM Strategi Pemilihan Supplier Dengan Metode ANP Dan TOPSIS Pada PT. Delta Graha Makmur (Grha Delta) - Wibisono, Deny; Rahman, Arif; Widjajanto, Tulus (CV. Multi Kreasi Media, 2025)
Delta Graha Makmur faces challenges in selecting steel plate raw material suppliers due to a manual system that focuses solely on price, resulting in 30% delivery delays, inconsistent quality, unreliable supplier dependency, as well as increased costs and production disruptions. This study aims to develop an ANP-TOPSIS-based supplier selection system to evaluate structured criteria such as quality, timeliness, price, and reliability. The objectives include: (1) formulating recommendations for the best suppliers with TOPSIS scores >0.8, (2) reducing production delays by 40% within three months post-implementation, and (3) developing a training module for the procurement team. The research method is carried out in four stages over 12 weeks: ANP modeling through interviews, performance data collection from five suppliers, TOPSIS analysis and simulation, as well as system implementation and training. The expected outcomes are improved supplier selection efficiency and reduced negative impacts on production.